Karakteristik Pasien dengan Keputusan Pembelian Jasa Layanan Kesehatan Gigi dan Mulut - Susilawati Susilawati; Nyoman Anita Damayanti (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to analyze the relationship between patient characteristics, including gender, age, education level, occupation, and dental health values ​​, with the decision to purchase dental and oral health services. The research method used in this research is analytic observational with a cross-sectional study design. The results showed that most of the dental clinic patients were female as much as 73.8%, adult age was 82.2%, middle education was 60.7%, students were 68.2%, and the value of moderate dental health was 55, 1%. There is a significant relationship between the amount of dental health (p-value = 0.024) and the decision to purchase dental and oral health services, while gender, age, education level, and occupation show no significant relationship. In conclusion, patient characteristics in dental health values ​​determine patients in making decisions related to purchasing dental and oral health services. Keywords: Patient Characteristics, Purchase Decisions, Dental Health